International Training For Publishing Scientific Works In Reputable International Journals: A Case Study In Indonesia And Sudan - Al-Maamari, Abdulwahab Abdullah; Deik, Ghiyas Ahmed; Ghazali, Ziyadul Ifdhal; Salam, Abdus; Syaripudin, Mohamad; Sobirin, Sobirin; Irpani, Ayit; Mabrurrosi, Mabrurrosi; Ulum, Bachrul; Mahmud, Basri (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The proliferation of global academic discourse necessitates the effective dissemination of scientific research through reputable international journals. This study investigates an international training program aimed at enhancing the capabilities of researchers in Indonesia and Sudan for publishing in high-impact journals. The training program focuses on equipping participants with essential skills in manuscript preparation, understanding international journal standards, and navigating the publication process. Through a case study approach, the research assesses the program’s effectiveness in improving participants' publication outcomes and the implications for their respective academic institutions. The findings reveal that the training significantly enhanced participants' proficiency in crafting high-quality manuscripts, aligning with international journal criteria, and successfully navigating the peer-review process. Participants reported increased confidence and competence in their writing and submission practices, contributing to a higher rate of successful publications in reputable journals. Additionally, the program fostered greater collaboration and knowledge exchange between researchers from Indonesia and Sudan, promoting a more integrated global academic community. This study underscores the value of targeted international training programs in bridging gaps in academic publishing practices and strengthening the global presence of researchers from diverse contexts. The implications for policy and practice include the need for continued support and development of such training initiatives to further advance the quality and impact of scientific research on a global scale.